Early monocyte response following local ablation in hepatocellular carcinoma - Kimm, Melanie A.; Kästle, Sophia; Stechele, Matthias M. R.; Öcal, Elif; Richter, Lisa; Ümütlü, Muzaffer R.; Schinner, Regina; Öcal, Osman; Salvermoser, Lukas; Alunni-Fabbroni, Marianna; Seidensticker, Max; Goldberg, S. Nahum; et al. (Frontiers in Oncology, 2022)
Local ablative therapies are established treatment modalities in the treatment of early and intermediate stage hepatocellular carcinoma (HCC). Systemic effects of local ablation on circulating immune cells may contribute to patients' response. Depending on their activation, myeloid cells are able to trigger HCC progression as well as to support anti-tumor immunity. Certain priming of monocytes may already occur while still in the circulation. By using flow cytometry, we analyzed peripheral blood monocyte cell populations from a prospective clinical trial cohort of 21 HCC patients following interstitial brachytherapy (IBT) or radiofrequency ablation (RFA) and investigated alterations in the composition of monocyte subpopulations and monocytic myeloid derived suppressor cells (mMDSC) as well as receptors involved in orchestrating monocyte function. We discovered that mMDSC levels increased following both IBT and RFA in virtual all patients. Furthermore, we identified varying alterations in the level of monocyte subpopulations following radiation compared to radiofrequency ablation. Liquid biopsy of circulating monocytes in the future may inform on the inflammatory response towards local ablation as part of an orchestrated immune response.